Managing User-centric Adaptive Services for Pervasive Computing - Wade, Vincent; Lewis, David; BRADY, AOIFE (IEEE Press, 2004)
Pervasive computing environments need to exhibit highly adaptive behavior to meet the changing task requirements and operational context of visiting mobile users. However this must be balanced with the need of resource owners to meet their goals in administering how users use their resources. This presents challenges of how to manage adaptive systems and how such management should be exercised by people, both average pervasive computing users and administrators of pervasive computing resources. This paper presents some of the issues involved in reconciling dynamic user-centric adaptation with the management of autonomic systems to meet high-level management policies. It discusses our architectural approach and presents some initial research results in addressing these issues
IEEE International Conference on Autonomic Computing
PUBLISHED
New York, USA
Keywords: Computer Science; Digital Engagement